The identification of copy number variation of CNV esv27061 among young adults with hypertension: preliminary findings - Shaik Alaudeen, Siti Radziah; Mohd Shah, Azarisman Shah; A.Talib, Norlelawati; Abdullah, Aszrin (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia., 2017)
Introduction: Hypertension related morbidities and mortalities around the world show a gradual increase and early detection and prevention are advocated. The Database of Genomic Variants (DGV) has associated variation in DNA sequences called copy number variation (CNV) with susceptibility to common diseases. However, little is known about CNV role in essential hypertension. Thus, this study aimed to characterize the CNV esv27061 among prehypertensive and hypertensive young adults in Malaysia.